Mechanism and clinical implication of gut dysbiosis in degenerative abdominal aortic aneurysm: A systematic review - Ernest S.H. Chui; Aidan K.Y. Chan; Anson C.K. Ng; Margaret Y.M. Teh; Haris C. Ho; Yiu Che Chan (Asian Journal of Surgery)
The gut microbiome is the entirety of microorganisms and their genomes residing in the gut, characterised by diversity, stability, and resilience. Disrupted gut microbiome has been implicated in multiple disease entities. The aim of this paper is to summarise the rapidly evolving contemporary evidence of gut dysbiosis on the development and progression of abdominal aortic aneurysm (AAA), discuss possible mechanisms, and explore potential microbiota-targeted interventions and prognostic markers for AAA. A systematic literature search was performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement, using PubMed, ScienceDirect, Web of Science, Ovid, Embase. Search terms of “microbiome” OR “dysbiosis” OR “microorganism”; AND “aneurysm” OR “dilatation” OR “aorta” were used. Study endpoints included effects of microbiota on AAA formation, effects of specific type of bacteria and its metabolite on AAA formation, and pre- or post-treatment by novel small-molecules/inhibitors. From May to August 2023, a total of twelve animal studies and eight human studies were included. Akkermansia muciniphila, Lactobacillus acidophilus and species from the Bacteroidetes phylum were associated with lower AAA incidence in both animal and human studies, while Proteobacteria phylum, Campylobacter, Fusobacterium and Faecalibacterium prausnitzii were found to be in abundance in the AAA group and were associated with larger aneurysms. The diversity of gut microbiota was inversely correlated with AAA diameter. Three important mechanisms were identified: including trimethylamine N-oxide pathway, butyric acid pathway, and aberrant tryptophan metabolism. With our expanding knowledge of the downstream pathogenic mechanisms of gut dysbiosis, novel therapeutics such as short-chain fatty acids and spermidine, as well as prognostic biomarkers such as TMAO have yielded promising preclinical results. In conclusion, there is strong evidence corroborating the role of gut dysbiosis in the pathogenesis of AAA, wherein its therapeutic and prognostic potential deserves further exploration.